The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/eurheartj/ehi252
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and heart rate variability predict long-term cardiac mortality after myocardial infarction

Abstract: Anxiety and emotional sensitivity were significant predictors of 8-year cardiac mortality after AMI. Reduced HF power, a recognized marker of vagal withdrawal, increased the risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 27 publications
4
42
1
Order By: Relevance
“…Time domain measures; SDNN [9,10], RMSSD [28] and frequency domain measures; HF [7,15] and LF [3,13,27] all hold prognostic value for CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Time domain measures; SDNN [9,10], RMSSD [28] and frequency domain measures; HF [7,15] and LF [3,13,27] all hold prognostic value for CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the latter study was cross-sectional and did not evaluate the relative impact of inhibition and HRV on health outcomes. However, a more recent study conducted in MI patients puts into question whether HRV mediates the relationship between inhibition and clinical outcome, as both social inhibition and impaired HRV were independent risk factors for mortality and non-fatal MI at 8 years follow-up [43]. Of note, patients with both risk factors had a substantially higher mortality rate (62%) compared with patients with no risk factors (6%) [43].…”
Section: Psychophysiological Stressmentioning
confidence: 99%
“…However, a more recent study conducted in MI patients puts into question whether HRV mediates the relationship between inhibition and clinical outcome, as both social inhibition and impaired HRV were independent risk factors for mortality and non-fatal MI at 8 years follow-up [43]. Of note, patients with both risk factors had a substantially higher mortality rate (62%) compared with patients with no risk factors (6%) [43]. Studies investigating the global Type D construct, HRV and their respective influence on clinical outcome are now warranted.…”
Section: Psychophysiological Stressmentioning
confidence: 99%
“…Ode et al (2010) reported that HRV was not associated with Neuroticism, though only used a brief ten-item scale to represent the more multifactorial construct of Neuroticism. Carpeggiani et al (2005) reported only one positive correlation between eight HRV measures and Cattell's 16 personality factors (insecurity and tension). Using the Tridimensional Personality Questionnaire, Huang et al (2013) found few significant relationships between five HRV indices and 15 personality subscales, even when males and females were examined in isolation, with only a 'harm avoidance' subscale returning a significant negative correlation.…”
Section: Introductionmentioning
confidence: 96%